Novel adjuvants in allergen-specific immunotherapy: where do we stand? - Lin, Yen-Ju; Zimmermann, Jennifer; Schülke, Stefan (Frontiers in Immunology, 2024)
Type I hypersensitivity, or so-called type I allergy, is caused by Th2-mediated immune responses directed against otherwise harmless environmental antigens. Currently, allergen-specific immunotherapy (AIT) is the only disease-modifying treatment with the potential to re-establish clinical tolerance towards the corresponding allergen(s). However, conventional AIT has certain drawbacks, including long treatment durations, the risk of inducing allergic side effects, and the fact that allergens by themselves have a rather low immunogenicity. To improve AIT, adjuvants can be a powerful tool not only to increase the immunogenicity of co-applied allergens but also to induce the desired immune activation, such as promoting allergen-specific Th1- or regulatory responses. This review summarizes the knowledge on adjuvants currently approved for use in human AIT: aluminum, calcium phosphate, microcrystalline tyrosine, and MPLA, as well as novel adjuvants that have been studied in recent years: oil-in-water emulsions, virus-like particles, viral components, carbohydrate-based adjuvants (QS-21, glucans, and mannan) and TLR-ligands (flagellin and CpG-ODN). The investigated adjuvants show distinct properties, such as prolonging allergen release at the injection site, inducing allergen-specific IgG production while also reducing IgE levels, as well as promoting differentiation and activation of different immune cells. In the future, better understanding of the immunological mechanisms underlying the effects of these adjuvants in clinical settings may help us to improve AIT.